Penggunaan Metode Role Playing Terhadap Kemahiran Bahasa Arab Siswa Kelas VII Mts Nurul Ikhwan Desa Dagang Krawan Kec. Tanjung Morawa Kab. Deli Serdang - Muhammad Candra Wibowo Sembiring (Fakultas Agama Islam, 2021)
The Role Playing method is a way of mastering the subject matter through the development of students' imagination and appreciation. The development of imagination and appreciation is carried out by students by playing them as living figures or inanimate objects. The purpose of the Role Playing Method or role playing is to teach students about empathy. Students are invited to experience the world by seeing it from the perspective of others. Students to imagine themselves in the position of others in order to be able to explore the feelings and attitudes shown by others, in the sense of playing the role of other people who may be different from the characteristics that exist in themselves. This research is quantitative research. The population of this study were all students in the school concerned, totaling 102 students with a research sample of 20 students. The method used is the questionnaire method as the basis of the research. The conclusion from the whole is obtained from the results of the test with a calculation which is 80.2. This shows that learning Arabic using the role playing method can improve student learning outcomes where previously the average value obtained only reached 71.15 and after applying the role playing method it increased to 80.28, which means an increase of 9.13. Thus, the answers to the formulated problems are drawn. The use of the role playing method can improve student learning outcomes in Arabic subjects. So it is very suitable for use by the school concerned.